Oracle GoldenGate 11g complete cookbook : over 60 simple and easy-to-follow recipes to perform various GoldenGate administration tasks such as installing, configuring, and maintaining GoldenGate replication /: over 60 simple and easy-to-follow recipes to perform various GoldenGate administration tasks such as installing, configuring, and maintaining GoldenGate replication. (2013) - Unknown
No abstract available